Penentuan Kandungan Unsur Aluminium, Mangan dan Silikon dalam Air Sungai Code Terhadap Waktu Sampling dengan Metode AANC - Hanim, Alfia; Azam, Much.; Hidayanto, Eko; Nuraini, Elin (BERKALA FISIKA, 2007)
An element determination which implied in river Code water below dr. Sardjito brigde with time variation was carried out using fast neutron analysis activation. Water river had been taken away from some dot later mixed, condensed by using an electrical stove from 500 ml to 7 ml. The sample then were iradiated by 14 MeV neutron from neutron generator and then were analyzed by gamma spectrometries.Â  The qualitative results shown that samples contents Al, Mn and Si. The quantitatively rate of element for aluminium is between 39,50-128,43 ppm, mangan between 71,54-182,80 and silicon between 19,12-84,53 ppm. Key words: FNAA, analysis element contents, Neutron Generator